Virtual reality and dementia (1998-2018): a systematic comparison between web of science and scopus - Sobral, M.; Pestana, M.H. (29th Alzheimer Europe Conference “Making valuable connections” – The Hague, Netherlands (23-25 October, 2019), 2019)
Despite Web of Science (WoS) and Scopus are widely consulted in research evaluations, there is no evidence about studies about virtual reality (VR) and dementia. In response this paper, by applying bibliometrics, analyses a set of 355 documents, 203 articles, 252 sources of publication, 189 journals, and 19,238 citations indexed in both platforms from 1998 to 2018. The results show differences in terms of scope, volume of data and coverage policies. For each new publication and citation in WoS there is 0.997 publications and 10.3 citation in Scopus. Compared to WoS, Scopus has a lower number of co-authors per document, article, journal and international collaboration, while covers more sources, documents and has a higher productivity rate and higher impact in the expansion of knowledge. Cyberpsychology and Behaviour is the top journal for Scopus while Journal of Alzheimer Disease is the correspondent one for WoS. USA and UK share the top of co-authorship in terms of national collaboration in Scopus, while for WoS is France. Instituto Auxologico Italiano and Aristotle University of Thesseloniki are in the top of affiliations respectively for Scopus and WoS. Both platforms converge of neuroscience has the main area of research, also considering: Riva and Magda Tsolaki have the most productive and h-index authors, USA as the top country with co-authorship international collaboration and in a relatively high growing trend of research. This paper contributes to the knowledge of characteristics and to the development of a field of research applying a bibliometric analysis through WoS and Scopus.